An Investigation of Physics Teachers' Multiple Representation Ability on Newton's Law Concept - Masrifah Masrifah; Agus Setiawan; Parlindungan Sinaga; Wawan Setiawan (Universitas Negeri Jakarta, 2020)
The ability of the teacher to represent a concept using various types of representation is a critical competency. Teachers who have limited multiple representation abilities will not be able to provide a holistic and appropriate learning experience because students have different abilities in constructing their knowledge. This study aims to determine the multiple representation ability of Physics teacher by using instruments to test multiple representations on the topic of Newton's law consisting of text representations, images, pictorial diagrams, tables, graphs, and mathematical equations. The subjects in this study were 30 high school Physics teachers in North Maluku who were determined based on the purposive sampling technique. Data on multiple teacher representation abilities were analyzed using descriptive statistics. The results of the data analysis showed that the multi-representation ability of high school physics teachers in Newton's law concept was in the medium category (55.7%) with the highest achievement occurring in the type of mathematical representation and the lowest in the pictorial diagram representation types for both female and male teachers. Besides, based on data implemented using SPSS 2.0, it can be concluded that there are no significant differences with the ability of teacher's multi-representation based on gender and teacher's teaching experience.